2020
DOI: 10.2147/idr.s269766
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Novel <em>bla</em><sub>CTX-M-65</sub>-Harboring IncHI2 Plasmid pE648CTX-M-65 Isolated from a Clinical Extensively-Drug-Resistant <em>Escherichia coli</em> ST648</p>

Abstract: Background: An ESBL, carbapenemase-and MCR-1-producing Escherichia coli ST648 strain was isolated from the urine sample of a patient in a Chinese tertiary hospital in 2016. Methods: The strain was fully sequenced by GridION X5 platform of Oxford Nanopore Technology. Results: The sequence analysis showed that the extended-spectrum β-lactamases CTX-M-65 and OXA-1, the carbapenemase NDM-5, the MCR-1 were encoded, respectively, by three different resistance plasmids. The pE648CTX-M-65-carrying bla CTX-M-65 was a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…We spot a strong association between Enterobacterieae and the enrichment of extended-spectrum β-lactamases and other ARGs in water from hospital surrounds, which differed from waters in wetlands where only 1-2 ARGs were carried by each species. This finding is consistent with previous studies that have reported frequent isolations of ESBL-carrying E. coli from riverine and surface water environments around hospitals (Dirar et al, 2020;Lü et al, 2020). The global dissemination of the bla CTX-M gene has been reported in hospital settings, communities, livestock, and companion animals (Jamborova et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…We spot a strong association between Enterobacterieae and the enrichment of extended-spectrum β-lactamases and other ARGs in water from hospital surrounds, which differed from waters in wetlands where only 1-2 ARGs were carried by each species. This finding is consistent with previous studies that have reported frequent isolations of ESBL-carrying E. coli from riverine and surface water environments around hospitals (Dirar et al, 2020;Lü et al, 2020). The global dissemination of the bla CTX-M gene has been reported in hospital settings, communities, livestock, and companion animals (Jamborova et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The similar IncX3 plasmids found in this study further highlight the importance of the epidemic IncX3 plasmid in the spread of the bla NDM-5 gene within the entire ecosystem. IncHI2/ST3 plasmids have been reported to mediate the transfer of various antibiotic resistance genes (ARGs), such as fosA3 ( Wang et al, 2020 ), floR ( Cao et al, 2020 ), bla CTX-M ( Lü et al, 2020 ), and mcr ( Long et al, 2019 ; Zhi et al, 2016 ), as well as various NDM-type carbapenemase genes, such as bla NDM-1 , bla NDM-9 , and bla NDM-4 ( Liu et al, 2017 ; Oueslati et al, 2021 ). However, there are very few reports of bla NDM-5 -carrying IncHI2 ( Ma et al, 2021 ; Zhao et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The IncHI2 plasmid is one of the most prevalent mcr-1 -bearing plasmid types, and IncHI2 plasmids are usually MDR plasmids carrying various resistance genes and insertion sequences (ISs) ( 6 , 7 ), especially IS 26 , which is related to cointegration of plasmids ( 8 , 9 ). Importantly, the IncHI2 plasmids were also important vectors for bla NDM-5 , bla CTX-M-65 , and bla OXA-1 , which were great threats to public health ( 10 , 11 ). Plasmid-mediated tigecycline resistance genes tet (X3) and tet (X4) were discovered in China in 2019 ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%